New records of the adventive land snail Helix lucorum (Gastropoda: Helicidae) in Kazakhstan - Temreshev, Izbasar I.; Makezhanov, Arman M.; Yakovleva, Natalya A.; Sadvakassov, Erlan; Kozhabayeva, Gulnar Ye.; Beknazarova, Zibasch B.; Isina, Zhanna M. (Altai State University, 2024)
Snail Helix lucorum Linnaeus, 1758, was first found on the territory of Kazakhstan in 2020. This species is invasive for the country. A stable population of the snail has been discovered in parklands in Kentau and Shymkent cities in the Turkistan oblast, in the city of Taraz in the Jambyl oblast, South Kazakhstan, and in the Almaty city in the South-East Kazakhstan. The nearest point where H. lucorum lives is the city of Tashkent (Uzbekistan), where this species was found in 2012. According to the local residents, tree seedlings were brought from Tashkent for landscaping the cities of Kentau and Shymkent. Thus, Tashkent was the most probavle source of the invasion. Further dispersal of H. lucorum in the South and South-East Kazakhstan, on the territory of Turkestan, Jambyl and Almaty oblasts is expected.